Phospholipids and peroxisomes in ferroptosis: the therapeutic target of acupuncture regulating vascular cognitive impairment and dementia - Zhang, Wenyu; Li, Ruiyu; Lu, Donglei; Wang, Xinliang; Wang, Qiuxuan; Feng, Xuyang; Qi, Sai; Zhang, Xuezhu (Frontiers in Aging Neuroscience, 2025)
Ferroptosis, since its conceptualization in 2012, has witnessed an exponential growth in research interest over recent years. It is regulated by various cellular metabolic pathways during chronic cerebral ischemia and hypoxia, including reactive oxygen species (ROS) generation, iron accumulation, abnormalities in glutathione metabolism, and disruptions in lipid and glucose metabolism. With the deepening and widespread research, ferroptosis has emerged as a critical pathway in the pathogenesis of vascular cognitive impairment and dementia (VCID). This unique cell death pathway caused by iron-dependent phospholipid peroxidation is strongly related to VICD. We examine the impact of phospholipid composition on neuronal susceptibility to ferroptosis, with a particular focus on the critical role of polyunsaturated fatty acids (PUFAs) in this process. Intriguingly, peroxisomes, as key regulators of lipid metabolism and oxidative stress, influence the susceptibility of neuronal cells to ferroptosis through the synthesis of plasmalogens and other lipid species. In this Review, we provide a critical analysis of the current molecular mechanisms and regulatory networks of acupuncture for ferroptosis, the potential functions of acupuncture in peroxisomal functions and phospholipid metabolism, and its neuroprotective effects in VCID, together with a potential for therapeutic targeting. As such, this highlights the theoretical basis for the application of acupuncture in VCID through multi-target regulation of ferroptosis. This review underscores the potential of acupuncture as a non-pharmacological therapeutic approach in VCID, offering new insights into its role in modulating ferroptosis and associated metabolic pathways for neuroprotection.